Management Accounting / Text and Cases - Dearden John (Prentice Hall, 1988)
Preface, Introduction, Cost Accounting Systems, An Introduction to Manufacturing Cost Accounting Systems, Standard Cost Accounting Systems, Historical and Combination Cost Accounting, Assigning Overhead Costs to Products, Miscellaneous Tpics in Cost Accounting, Decision Support Systems, Decision Support Systems: Tactical Marketing Decisions, Decision Support Systems: Disinvestment Decisions, Decision Support Systems: Capital Investment Decisions, Financial Control Systems, Manufacturing Cost Varriance Analysis, Financial Control of Manufacturing Overhead Expenses, Financial Control of Discretionary Expenses, Profit Analysis, Management Control Systems, Profit Centers, Transfer Pricing, Measurement of Performance, Cost Accounting and Control in Service Industries, Comprehensive Cases.
Preface, Introduction, Cost Accounting Systems, An Introduction to Manufacturing Cost Accounting Systems, Standard Cost Accounting Systems, Historical and Combination Cost Accounting, Assigning Overhead Costs to Products, Miscellaneous Tpics in Cost Accounting, Decision Support Systems, Decision Support Systems: Tactical Marketing Decisions, Decision Support Systems: Disinvestment Decisions, Decision Support Systems: Capital Investment Decisions, Financial Control Systems, Manufacturing Cost Varriance Analysis, Financial Control of Manufacturing Overhead Expenses, Financial Control of Discretionary Expenses, Profit Analysis, Management Control Systems, Profit Centers, Transfer Pricing, Measurement of Performance, Cost Accounting and Control in Service Industries, Comprehensive Cases.